THE CHARACTERISTIC CHANGES OF PROTEASE CG-10 IMMOBILIZED BY BENTONITE - Rudiana Agustini (Universitas Gadjah Mada, 2005)
The CG-10 isolate is a thermophile microorganism live in extreme environments, a hot spring located at Cangar East Java, having temperature 50 oC. The isolate had following characteristics: rod shaped cells, gram-positive, size of cells 6-14 µm, aerobic, and obligate thermophile. Based on the nucleotide sequences of its 16S-rRNA gene indicated that these isolate was closely related to Bacillus caldoxylolyticus (98.305% sequence similarity). The enzymes produced by thermophile microorganism were usually active at a higher temperature than that of the environment in which they live. Therefore it is possible to use this enzyme in industries requiring high temperature in their production processes. The CG-10 isolate grew well in a liquid waste of tofu and could secretion extracellular protease. The protease was isolated by fractioning at 35% (w/v) ammonium sulfate, centrifuged at 4000 rpm for 15 minutes, and had the following characteristics: optimum temperature 80 oC, optimum pH 8, the molecular weight 53.000-76.000 Dalton (for the protease showing the highest activity), pHI value between 7.5 up to 8.2, and could be classified as a serine alkaline protease. For increasing the efficiency of this protease in industries had been done by immobilization with bentonite. The immobilization process is done at optimum pH (pH 5). The characteristic changes research of protease CG-10 isolate immobilized by bentonite had been done. The immobile enzyme showed different characteristics for that of the native (mobile enzymes). The immobile enzyme showed a different optimum temperature, a higher heat resistance but the same optimum pH as the native enzyme.